Financial instruments: definition, recognition, classification, evaluation and disclosure of financial statements (Journal of Economic Research & Business Administration, 2016)
Problems and difficulties of the financial support of investment pro-cesses generate the need to update the theoretical-methodological basis of the investment, in particular in the accounting records: the concept of recognition, classification and measurement of financial instruments. Problems of accounting for financial instruments in accordance with IAS become particularly relevant for Kazakhstan specialists on accounting. The article examines the main issues related to the recognition, evaluation, and taking into account the classification and measurement of financial assets and liabilities and disclosure of financial instruments. Showing: 1) and tak-ing into account the specific features of categories of financial instruments in the accounts in accordance with the standard chart of accounts for the formation of indicators of the reporting in accordance with IFRS.2) the dis-closure of information in accordance with the provisions of IAS 32 to IFRS (IAS) 32 Financial Instruments: Presentation and Disclosures and IAS (IFRS) 7 “Financial Instruments - Disclosures”.
Keywords: Investments IFRS; financial instruments; financial assets; financial liabilities; derivatives are recognized; evaluation; Classification.